Pengelolaan Pembelajaran Pendidikan Jasmani, Olahraga dan Kesehatan Kelas BIO (Bakat Istimewa Olahraga) Berbasis Prestasi (Studi Kasus di SMAN I Slogohimo) - Kasto, Kasto, Dr.Sabar Narimo, M.M., M.Pd, Dr.Suyatmini,SE.,M.Si (2016)
The Objectives of this study are (1) to describe the Planing an instructional of Physical Education, Sport and Health ( a case study at SMAN I Slogohimo) (2) to describe the material of an instruction Administration of physical education sports and health in BIO class at SMAN I Slogohimo. (3) to describe an evaluation of an instruction learning Administration physical education sport and health in BIO class at SMAN I Slogohimo. The location of this study at SMAN I Slogohimo. The kind of this study is qualitative research with an approach of etnografi. Technique of collection data using an observation data, in depth interviews and an analysis method document. Model of data analysis in this study using the methods of data analysis are displayed in the sites of description. The result of this study are (1) the planning of an instructional Administration of physical education sport and health at SMAN I Slogohimo include three aspects, they are the prosess of students selection, curriculum and infrastructure in general has met the term and condition in the theory so it is going well. (2) the implementation of an instructional learning Administration of physical education sportsand health at SMAN I Slogohimo includes three aspects, ramely an appointment of the teacher, teaching learning activity, quidance and counseling service in general has met the term and conditions in the exiting theory so that can run well. (3) The evaluation of an instructional learning Administration of physical education sports and health at SMA Negeri I Slogohimo to access the succesfull of the Sekolahby doing an evaluation continuously sof each and of the year. After organized BIO class there is an increase of an achievement sports in both in district and regional level.